Pengaruh Ekstrak Etanol Daun Kemangi (Ocimum sanctum L.) Terhadap pH dan Tukak Lambung Pada Tikus Putih Jantan - Sri Oktavia; Helmi Arifin; Ria Irawati (STIFARM Padang, 2015)
The effect of basil (Ocimum sanctum L.) leaf ethanolic extract on pH and gastric ulcers in male rats induced by ethanolic absolute 1 mL /200 g BW orally has been evaluated. The observed parameters where pH change gastric liquid and ulcer index value. The result indicated that the basil (Ocimum sanctum L.) leaf ethanolic extract at doses of 100 mg/KgBW. 300 mg/KgBW and 900 mg/KgBW significantly decreased the ulcer index with curative ratio where 45.82 %, 62.94 % and 80.65 % (for one time given extracts for two days), 49.13 %, 77.69 % and 94.62 % (for one time given extract for four days) 52.71 %, 77.67 % and 97.21 % (for one time given extract for six days) compared to the positive control. The extracts at 100 mg/KgBW, 300 mg/KgBW and 900 mg/KgBW also significantly decreased the gastric acid pH to its normal value (P<0.05).